Women in sustainable watershed development - Mukhopadhyay, D. (2003)
Irrigated agriculture in India has reached its limit and further increased in food production must come from dry land farming, specially watershed development and management through community participation. One of the main situations in which participation among the rural people emerges is the existence of common problems, which forces the people to come together to take decisions regarding common action. For instance, soil erosion, paucity of fodder and fuel wood, scarcity of water for drinking and domestic use, loss of vegetation, etc. are the commonly perceived problems of rural women which should result in high level of their participation in watershed management programmes. Community mobilisation could also be viewed as an important mechanism through which the responsibilities of common property resource management could be transferred back effectively to the people so that more productive, sustainable and equitable development is possible. - Reproduced.
Keywords: Sustainable development; Women; Watersheds